State laws on youth access to tobacco in the United States: measuring their extensiveness with a new rating system - Alciati, M. (BMJ Group, 1998)
OBJECTIVE—To develop and implement a rating system evaluating the extensiveness of state laws restricting youth access to tobacco. DESIGN—State laws on youth access to tobacco were analysed and assigned ratings on nine items. Six items addressed specific tobacco-control provisions, and three related to enforcement provisions. For each item, a target was specified reflecting public health objectives. Achieving the target resulted in a rating of +4 points; for three items, a rating of +5 was possible if the target was exceeded. Criteria for lower ratings were established for situations when the target was not met. SETTING—United States. RESULTS—State scores (sum of the ratings across all nine items) ranged from 0-18 in 1993, 2-21 in 1994, and 1-21 in 1995 and 1996,( )out of a possible total of 39. The average score across states was 7.2 in 1993, 7.9 in 1994, 8.2 in 1995, and 9.0 in 1996. The overall mean rating (per item) was 0.80 in 1993, 0.88 in 1994,( )0.91 in 1995, and 1.00 in 1996, on a scale where 4.0 indicates that the target goals (per item) were met. From 1993 to 1996,( )scores increased for 20 states, decreased for one state, and remained unchanged for the others. The number of states for which state preemption of local tobacco regulation was a factor doubled from 10 states in 1993 to 20 states in 1996. CONCLUSIONS—Although all states have laws addressing youth access to tobacco, this analysis reveals that, as of the end of 1996, the progress towards meeting health policy targets is slow, and state legislation that preempts local tobacco regulation is becoming more common.   Keywords: adolescents; legislation; access laws; United States